The Menace of Dowry Related Problems in Kerala- A Study of Paravoor Municipality in Ernakulum district - Mohammed, Ajims P. (2015)
Dowry refers to “the property, money, ornaments or any other form of wealth which a man or his family receives from his wife or her family at the time of marriage .Dowry is both a practice and a problem with Indian marriage (Haveripeth, 2013)”. The practice of giving dowry was meant to assist a newly-wed couple to start their life together with ease; however, now it has become a commercial transaction in which monetary considerations receive priority over the personal merits of the bride. It is important to note that principle 4 of the Cairo Manifesto 1994 states, “the advancement of gender equality and equity, the empowerment of women, the elimination of all kinds of violence against women and the promotion of women’s control over their own fertility are the corner stones of human development. The human rights of women and girl child are inalienable, integral and indivisible part of universal human rights. The full and equal partnership of women in civil, cultural, economic, political and social life at the national, regional and international levels and the eradication of all forms of discrimination on grounds of sex are priority objectives of the international community “.From womb to tomb women are made to pay heavily for their womanhood, though protection of womanhood is a condition precedent for a just world order. Keywords: Dowry, Empowerment of women, advancement of gender equality